Plasmonic Nanostructures for Energy Application - Pathak, Nilesh Kumar (Frontiers in Mechanical Engineering, 2020)
The present work furnishes the optical properties of metal nanostructures and their application in energy. Metal supports plasmonic resonances which can be tuned in desired range of solar spectrum by changing its size, shape and surrounding environment. Two different systems, isolated and coupled gold metal nanosphere are taken into account to study the optical properties. These optical properties of chosen nanostructure are analysed in terms of surface plasmon resonances using Boundary Element Method (BEM). The tuning of surface plasmon resonances under different parameter domain and their applications in energy is the main thrust of this work. The simulated extinction spectrum and corresponding spectral width of metallic nanogeometries could be used in several applications like solar still, solar collector and solar cell.